A aposentadoria por invalidez da pessoa vivendo com o vírus HIV: pressupostos teóricos e pragmáticos à luz do paradigma do Estado democrático de direito - Valentim, Luana Petry (2015)
This is a qualitative and descriptive search, that begins with the purpose of analyze possible contradictions / divergences between judgments handed down by the Federal Regional Courts in cases involving retirement claims of people living with HIV / AIDS, and decisions of the Turma Nacional de Uniformização de Jurisprudência - TNU (Standardization National Panel of Jurisprudence) the attempt to standardize these cases became an important factor in changing decision during such legal proceedings of this nature. The initial hypothesis that the unification of jurisprudence would allow the achievement of a higher degree of justice and equal treatment for people with HIV, in order to unify judicial decisions, was not confirmed. The constant speeches in: judicial decisions in the sample, the TNU decisions, interviews with infectologists and people living with the virus, were submitted to analysis by methodological approach taking as a reference the thought of Robert Alexy. The analysis showed that the Unified Jurisprudence is incompatible with the scope of a fair justice and the guarantee of fundamental rights of people with HIV which claim disability retirement, since the portability of the virus by itself, does not enforce disability condition. Based on the theory of Alexy judgments involving clash of principles related to fundamental rights should be clarified considering the specific circumstances of an individual case, which does not allow standardization of case law. This observation, made possible through exploratory research conducted the initial phase of study and the first meetings with the research subjects, was instrumental in changing the investigation problem, and this becomes to be based on the search of theoretical and pragmatic assumptions that guide judgments. It was concluded that the need to seek standardization, not of jurisprudence, but of theoretical and pragmatic assumptions that can support the decision-making process of the judiciary in the face of the democratic rule of law paradigm. The research concludes with the presentation of some assumptions identified in the analyzed discourses and theoretical basis adopted.